Construction of a Shuttle Vector Using an Endogenous Plasmid From the Cyanobacterium Synechocystis sp. PCC6803 - Jin, Haojie; Wang, Yan; Idoine, Adam; Bhaya, Devaki (Frontiers in Microbiology, 2018)
To advance synthetic biology in the photosynthetic cyanobacterium Synechocystis sp. PCC6803 (Syn6803), we constructed a shuttle vector with some versatile features. This shuttle vector, pSCB-YFP, consists of a putative replicon identified on the plasmid pCC5.2, the origin of replication of pMB1 from E. coli, as well as the YFP reporter gene and a spectinomycin/ streptomycin resistance cassette. pSCB-YFP is stably maintained in Syn6803M (a motile strain that lacks the endogenous pCC5.2) and expresses YFP. In addition, we engineered a fragment into pSCB-YFP that has multiple cloning sites and other features such that this plasmid can also be used as an expression vector (pSCBe). The shuttle vector pSCB-YFP can be stably maintained for at least 50 generations without antibiotic selection. It is a high copy number plasmid and can stably co-exist with the RSF1010-based pPMQAK1-GFP.